A novel and simple workflow for investigating Mycoplasma spp. contamination in cell cultures - de Freitas Michelon, Nathalia; Júnior, José Valter Joaquim Silva; Weiblen, Rudi; Flores, Eduardo Furtado (Folia microbiologica, 2025)
Mycoplasma spp. contamination is a major concern in laboratories handling cell cultures, and routine detection methods are usually time-consuming, laborious and lack sensitivity. This study presents a streamlined workflow integrating rapid thermal DNA extraction (99 °C-1 min) with a SYBR Green-based qPCR for Mycoplasma detection. High-coverage primers targeting an 86-bp region of the 16S rDNA were designed using 109 Mycoplasma spp. sequences from GeneBank. In silico analysis confirmed full primer annealing to major cell culture contaminants (M. arginini, M. hominis, M. orale, and M. hyorhinis). Upon thermal lysis and qPCR optimization, the yield of the protocol was equivalent to that of phenol-chloroform extraction plus qPCR, with a detection limit of 64 bacterial cells. Finally, the performance of the protocol was confirmed in cell cultures with known Mycoplasma spp. contamination, accurately reproducing the contamination status. Thus, the developed protocol provides a simple, rapid, cost-effective, and sensitive method for monitoring Mycoplasma spp. in cell cultures.
Keywords: Cell Culture Techniques; průběh práce; Workflow; DNA primery; RNA ribozomální 16S; Mycoplasma; ribozomální DNA; buněčné kultury; DNA, Bacterial; DNA, Ribosomal; DNA bakterií; lidé; kvantitativní polymerázová řetězová reakce; DNA Primers; Humans; Real-Time Polymerase Chain Reaction; RNA, Ribosomal, 16S